Extensive osteolytic disease in the mandible of a pediatric patient: Case report - Fortuna, Tila; Rebouças, Deyvid Silva; Lopes, Gabriela Santos; Pimentel, Ana Carolina Lemos; Medrado, Alena Ribeiro Alves Peixoto; Freitas, Carlos Elias de (Journal of Oral Diagnosis, 2017)
Introduction: Gorham’s disease, correspond to a massive osteolytic disease of the bones, characterized by destruction and resorption of one or more bones, spontaneous and progressive. The etiology of the disease is still unknown. The destroyed bone does not have the ability to regenerate or repair and is replaced by dense fibrous tissue. Bones of the skull and pelvis are the most commonly affected and in maxillofacial bones, the mandible is particularly affected. Case report: This study reports the case of an 11-year- old female, referred to the Oral and Maxillofacial Surgery service showing extensive area of spontaneous bone resorption, in which only the alveolar portion of the mandibular symphysis and the head of the left jaw were present. The history and clinical features observed indicated Gorham’s disease. Final considerations: When in progressive stages Gorham’s disease is difficult to be diagnosed by histopathological evaluation, due to limited remaining bone quantity, leaving only clinical and complementary exams to make allowances. The treatment is controversial in the literature. Therapy is individualized in accordance with the severity of the patient’s condition and the site of involvement.